A review of the application of virtual reality technology in higher education based on Web of Science literature data as an example - Ding, Xiaoqin; Li, Zhe (Frontiers in Education, 2022)
In recent years, with the rapid development of information technology, the visualization and interaction of virtual reality technology has developed, making the application of VR technology in education more and more attractive to scholars. This paper adopts the literature analysis method, focusing on the application of VR technology in the field of higher education, selects 80 empirical studies in the Web of Science literature database, conducts in-depth reading and analysis of the papers, and summarizes the experience of applying VR technology in the field of higher education. In order to deepen the application of VR in higher education. The research results show that the research objects of VR application in higher education are mainly undergraduates, the main majors of application are science, engineering and medical related majors, and the application of humanities and social sciences is relatively rare. At present, the devices used for VR in higher education are mainly computers and headsets, which are not portable enough. In addition, students lack guidance and training in the use of VR equipment before class. Compared with traditional education, most of the studies show that the application of VR to higher education and teaching has positive effects, mainly by affecting students' behaviors to affect students' learning results. The researchers mainly use traditional evaluation methods to evaluate teaching effects, use questionnaires and tests to collect data, and use data analysis methods mainly difference analysis and descriptive analysis. Based on the research results, the researchers put forward some suggestions at the end of the paper.